Reflections on teaching database management systems to undergraduate students. (1st January 2011) - Saeed, Saqib; Aamir, Rizwan; Mahmood, Zaigham
Database management courses are an essential part of computer science curricula in educational institutions. Courses are normally well-designed, however, in order for students to better understand the theoretical concepts, hands-on practical sessions are also necessary. Such practice will help students to meet the challenges of job market and working in the industry. This paper suggests that group projects be used as a tool to make the teaching and learning of the subject area, more effective. In the paper, we first discuss the design of a course module and describe a pedagogical approach that was adopted to teach a database management systems (DBMS) course at a university in Pakistan and then analyse students' feedback comments to gauge the effectiveness of the teaching strategy. Our design proposes a detailed 16-week plan for the teaching of the subject. The current study also provides guidelines for the teaching staff intending to take on the responsibilities of delivering DBMS and similar courses.